Defining the influence of size‐exclusion chromatography fraction window and ultrafiltration column choice on extracellular vesicle recovery in a skeletal muscle model. Issue 4 (21st April 2023) - Fernández‐Rhodes, María; Adlou, Bahman; Williams, Soraya; Lees, Rebecca; Peacock, Ben; Aubert, Dimitri; Jalal, Aveen R.; Lewis, Mark P.; Davies, Owen G.
Abstract: Extracellular vesicles (EVs) have the potential to provide new insights into skeletal muscle (SM) physiology and pathophysiology. However, current isolation protocols often do not eliminate co‐isolated components such as lipoproteins and RNA binding proteins that could confound outcomes and hinder downstream clinical translation. In this study, we validated an EV isolation protocol that combined size‐exclusion chromatography (SEC) with ultrafiltration (UF) to increase sample throughput, scalability and purity, while providing the very first analysis of the effects of UF column choice and fraction window on EV recovery. C2C12 myotube conditioned medium was pre‐concentrated using either Amicon ® Ultra 15 or Vivaspin ® 20 100 KDa UF columns and processed by SEC (IZON, qEV 70 nm). The resulting thirty fractions obtained were individually analysed to identify an optimal fraction window for EV recovery. The EV marker TSG101 could be detected from fractions 5 to 14, while CD9 and Annexin A2 only up to fraction 6. ApoA1 + lipoprotein co‐isolates were detected from fraction 6 onwards for both protocols. Strikingly, Amicon and Vivaspin UF concentration protocols led to qualitative and quantitative variations in EV marker profiles and purity. Eliminating lipoprotein co‐isolation by reducing the SEC fraction window resulted in a net loss of particles, but increased measures of sample purity and had only a negligible impact on the presence of EV marker proteins. In conclusion, our study developed an effective UF+SEC protocol for the isolation of EVs based on sample purity (fractions 1–5) and total EV abundance (fractions 2–10). We provide evidence to demonstrate that the choice of UF column can affect the composition of the resulting EV preparation and needs to be considered when being applied in EV isolation studies in SM. The resulting protocols will be valuable in isolating highly pure EV preparations for applications in a range of therapeutic and diagnostic studies.